2004
DOI: 10.1523/jneurosci.3731-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Improvement and Decline in Tactile Discrimination Behavior after Cortical Plasticity Induced by Passive Tactile Coactivation

Abstract: Perceptual learning can be induced by passive tactile coactivation without attention or reinforcement. We used functional MRI (fMRI) and psychophysics to investigate in detail the specificity of this type of learning for different tactile discrimination tasks and the underlying cortical reorganization. We found that a few hours of Hebbian coactivation evoked a significant increase of primary (SI) and secondary (SII) somatosensory cortical areas representing the stimulated body parts. The amount of plastic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
89
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 24 publications
11
89
3
Order By: Relevance
“…In direct contrast, the present study shows in a neuropathic pain condition that does not involve deafferentation, trigeminal neuropathy, the S1 representation representing the thumb moves away from that of the lip. Similarly, it has been reported that painful carpel tunnel syndrome is associated with an increased representation of the painful digits (Napadow et al, 2006) and use-dependent enlargements of cortical representations, including those in response to increased innocuous tactile stimulation, have been shown to occur in many sensory systems (Hodzic et al, 2004). In contrast, complex regional pain syndrome, a non-deafferented pain condition, is associated with contraction of the relevant cortical representation (Maihöfner et al, 2003;Pleger et al, 2004), although this condition involves significant decreases in the use of the painful region, which may itself affect S1 organization.…”
Section: Discussionmentioning
confidence: 87%
“…In direct contrast, the present study shows in a neuropathic pain condition that does not involve deafferentation, trigeminal neuropathy, the S1 representation representing the thumb moves away from that of the lip. Similarly, it has been reported that painful carpel tunnel syndrome is associated with an increased representation of the painful digits (Napadow et al, 2006) and use-dependent enlargements of cortical representations, including those in response to increased innocuous tactile stimulation, have been shown to occur in many sensory systems (Hodzic et al, 2004). In contrast, complex regional pain syndrome, a non-deafferented pain condition, is associated with contraction of the relevant cortical representation (Maihöfner et al, 2003;Pleger et al, 2004), although this condition involves significant decreases in the use of the painful region, which may itself affect S1 organization.…”
Section: Discussionmentioning
confidence: 87%
“…An interesting question for future research is whether, to produce lasting acuity enhancement, tactile experience must be accompanied by focused attention such as occurs during Braille reading and other purposeful tasks. In this regard, it is noteworthy that prolonged, unattended vibratory stimulation reversibly improves fingertip spatial acuity (Godde et al, 2000;Hodzic et al, 2004).…”
Section: Evidence That Tactile Experience Drives Acuity Enhancementmentioning
confidence: 96%
“…Several lines of evidence link larger somatosensory cortical representations to better tactile spatial acuity. Three hours of low-frequency vibration applied to the index finger both enhanced spatial acuity and enlarged the finger's cortical representation (Hodzic et al, 2004). Although receptor density-at least for the relatively easily visualized Meissner corpuscles-is apparently conserved across digits (Dillon et al, 2001), the digits with a larger cortical representation also have better acuity (Duncan and Boynton, 2007).…”
Section: Possible Neural Mechanismsmentioning
confidence: 99%
“…Wickens states that "extensive perceptual experience" and consistency of responses are necessary ingredients for a task to become automatic. Furthermore, extensive training helps to eliminate decrease in sensitivity [76] and improves task performance by improving tactile discrimination and increasing activation of the somatosensory cortical areas representing the stimulated body part [119].…”
Section: Introductionmentioning
confidence: 99%